Implementasi Pembelajaran Pendidikan Pancasila Kelas IV: Integrasi Model PBL dengan Media Diorama Roda Putar Materi Norma - Ramadhani, Alifia Yoranika; Puspita, Ari Metalin Ika (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2026)
Pancasila Education plays a crucial role in shaping students’ character, attitudes, and understanding from the elementary level. However, teacher-centered learning practices often lead to passive student en-gagement and low learning outcomes. Therefore, interactive and contextual learning innovations are needed. This study aims to de-scribe the implementation of the Problem Based Learning (PBL) model integrated with the Spinning Wheel Diorama media on the topic Norms in My Life and to measure its effectiveness in improving stu-dents’ learning outcomes.This research employed Classroom Action Research (CAR), conducted in two cycles with 20 fourth-grade students of Class IV A at UPT SDN 162 Gresik. Data were collected through observation, teacher interviews, and learning outcome tests, then analyzed using average score calculations and mastery percentages based on the Minimum Mastery Criteria (MMC).The results showed a significant increase from an average score of 41.5 (15% mastery) in the pre-test to 78.5 (90% mastery) in the post-test. These findings confirm that integrating PBL with the Spinning Wheel Diorama media can enhance students’ understanding of normative concepts while fostering an active, collaborative, and meaningful learning atmosphere. In addition, responses from both students and teachers indicate that this method is relevant for connecting theoretical knowledge with re-al-life practice.In conclusion, PBL-based learning supported by concrete media such as dioramas is effective in improving the quality of Pancasila Education learning. Future research is recommended to explore the application of similar models in other subjects and to examine students’ affective and psy-chomotor aspects in greater depth.